US Accreditation: Bridging the International and National Dialogue Gap - Eaton, Judith (International Higher Education, 2008)
Throughout this decade, international conversations about higher education have been punctuated with significant attention to accreditation and quality assurance. While the central and often dominant in these deliberations is accreditation as practiced in the United States, its operation and accomplishments. States. While the international conversation often focuses on the operation and accomplishments of American accreditation systems, there is a robust US national dialogue underway focused almost exclusively on the limitations of accreditation. Understanding these concerns can be beneficial to both developing countries and the United States.